Extensive Reading on Wattpad and Its Benefits to Students' English Skills: Students' Perceptions - Intan Permatasari; Agus Wijayanto; Diah Kristina (Hasanuddin University, 2020)
The purpose of this study was to explore students’ perception’s towards Extensive Reading on Wattpad platform as well as its benefits to students’ English skills. Extensive Reading enables students to read a great deal amount of reading materials based on their personal interests and level of comprehension which is actually applied outside the class room for most people consider it as reading for pleasure. It has also been known that Extensive Reading has many benefits in improving students’ language skills. The advancement of technology over the years allows people to do many activities online, including Extensive Reading activity. Thus, Wattpad is considered to have enormous and various reading materials that can support extensive reading for the students. This study is a case study. The data were obtained from an in-depth interview with the participant who were two undergraduate students majoring English Education from a state university in Indonesia. The participants were selected purposively for the reason they were known to have been doing extensive reading activity on Wattpad for a quite long time, specifically for more than three years. The research findings showed that students have positive perceptions towards Extensive Reading on Wattpad which are categorized into three elements namely cognitive, affective, and conative. Four notable benefits of Extensive Reading on Wattpad were also mentioned by the students such as it contributed in unconsciously improving students’ writing skills, vocabulary mastery, speaking skills, as well as listening skills.